Observations on helminth infections of free-living and captive rheas (Rhea americana) in Brazil - Zettermann, C. D.; Nascimento, A. A.; Tebaldi, J. A.; Szabo, MJP (Elsevier B.V., 2005)
The present work describes helminth infection of eight free-living and 12 captive rheas (Rhea americana) from, respectively, Pantanal of Mato Grosso do Sul State, and Jaboticabal, São Paulo State, Brazil. Captive birds were young and had a high mortality rate, while free-living birds were adult and apparently healthy. Infections were evaluated by post-mortem examination of internal organs and recovery of helminths using standard parasitological procedures. Seven species of nematodes (Sicarius uncinipenis, Torquatoides crotophaga, Deletrocephalus dimidiatus, D. cesarpintoi, Paradeletrocephalus minor, Capillaria venteli and Dicheilonema rheae) and two species of cestodes (Houttuynia struthionis and Chapmania tauricolis) were identified. P. minor, which inhabits the large intestine, was the most common helminth in free-living birds (63.9%). In captive rheas, a mean parasitic load of 173 helminths per host was found. The gizzard of these birds was the most parasitized organ and S. uncinipenis was most common (92.5%). Parasitism of free-living and captive birds and associated pathology are discussed. (c) 2005 Published by Elsevier B. V.
Keywords: Rhea americana; epidemiology; helminths; prevalence; Brazil